Death by Frostbite: From Theory to Reality: A Case Report - Stefano Duma; Federica Mele; Mariagrazia Calvano; Mirko Leonardelli; Enrica Macorano; Giovanni De Gabriele; Alessandro Cristalli; Andrea Marzullo; Francesco Introna (Forensic Sciences)
Background: When the body temperature falls below 35 °C, a condition known as hypothermia occurs. This renders it impossible to regulate the body temperature and produce heat. In these cases, death is due to a cessation of vital functions and is triggered by a body temperature below 25 °C. A multidisciplinary approach is typically required when hypothermia is suspected to combine circumstantial evidence, external examination, autopsy, microscopic and biochemical findings, and other data useful to assess the diagnosis of fatal hypothermia. Post-mortem diagnosis of death by hypothermia frequently presents a medico-legal dilemma. Methods and Results: The authors present a case of hypothermia in which site inspection, autopsy, and histological examination simultaneously revealed the forensic and anatomopathological characteristic findings of hypothermia with some peculiar evidence: paradoxical undressing, thanatochronological phenomena, frost erythema, polyvisceral congestion and Wischnewski spots, and subnuclear vacuolization of renal tubular epithelial cells.